Soros : tajemnica sukcesu najwiekszego inwestora swiata - Slater, Robert, 1943- (Warszawa : Wydawn. Wiedza i Zycie, 1996)
The biography of a noted financial investor, George Soros.
Keywords: Soros, George; Capitalists and financiers -- Biography; Investments